PENGARUH TINGKAT EKONOMI RUMAH TANGGA DAN TINGKAT PENDIDIKAN LINGKUNGAN BERMAIN TERHADAP MINAT MELANJUTKAN SEKOLAH SISWA KELAS IX SMPN 1 KARANGREJO - Uci Sulistiyani,; Nafik Umurul Hadi (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2018)
In this study, students of class IX SMPN 1 Karangrejo who are in rural school environment and precisely in mountainous environment have a tendency to not continue to the next school by reason of geographical area. This is known by the large number of school-aged children who only graduated in the junior secondary level. The phenomenon is somewhat indisputable with some students who still continue to high school in Karangrejo subdistrict with a number that is not much. In this study the formulation of the problems to be sought to pursue the scope of the study are: How Influence of Household Economy Level on Interest Continuing School Students Class IX SMPN 1 Karangrejo? How Does the Level of Environmental Education Play to Interest Continuing School Students Class IX SMPN 1 Karangrejo? How Influence Household Economic Level and Level of Environmental Education Play to Interest Continuing School Students Class IX SMPN 1 Karangrejo? The research method used is quantitative, the instrument of this study is a questionnaire, the population of this study students class IX SMPN 1 Karangrejo, sample research as many 66 students. The analysis used is linear regression with hypothesis analysis is t test and F test. There is Effect of Household Economy Level on Interest Continuing School Students Class IX SMPN 1 Karangrejo. There is no effect of Level of Environmental Education Playing to the Interest Continuing School Students Class IX SMPN 1 Karangrejo. There is Influence of Household Economy Level and Level of Environmental Education Playing to Interest Continuing School Student Class IX SMPN 1 Karangrejo.